Interprofessional curriculum development achieves results: Initial evidence from a dementia-care protocol. Issue 3 (3rd May 2016) - Annear, Michael James; Goldberg, Lynette R.; Lo, Amanda; Robinson, Andrew
ABSTRACT: This report describes the outcomes of a five-day, protocol-based interprofessional education (IPE) initiative to prepare undergraduate medical, nursing, and paramedic students for collaborative work with adults with dementia. Clinical placements provided a structured and supervised IPE experience for 127 students in two Residential Aged Care Facilities (RACFs) in Hobart, Australia, during 2013 and 2014. The IPE activity was based on a seven-step protocol formulated by an interprofessional team of educators and aged care practitioners that revolved around collaborative assessments of adults with complex health needs. This article describes the IPE protocol and presents the results of a pre- and post-placement attitude questionnaire and knowledge quiz administered to evaluate student attitudes towards IPE and knowledge of dementia. Data suggest that a five-day, supervised, and protocol-based IPE experience in a dementia-care setting can inculcate positive changes in student attitudes about collaborative practice and may encourage dementia-related learning outcomes.